Mapping the double-strand breaks at the mating-type locus in fission yeast by genomic sequencing. - Nielsen, O (1989)
In fission yeast mating-type switching is initiated by the formation of a double-strand DNA break at the mating-type locus. A prerequisite for generation of the break is some 'imprinting' of the DNA in the previous cell cycle. We have used the technique of genomic sequencing to map the position of the break directly on chromosomal DNA cleaved in vivo. On one strand the break is situated very close to the right-hand border of the expressed mat1 cassette. Cells of opposite mating type, P and M, have their breaks at slightly different positions on this strand. On the other DNA strand of both alleles the ends are probably masked by tightly bound proteins and therefore the precise nature of the break could not be determined. Since the break is stable throughout the cell cycle, these proteins may function in vivo to confer structural stability on the chromosomes having the break. The implications of these findings for models of mating-type switching are discussed.